Hydrophosphonylation of activated alkenes and alkynes via fluoride ion activation in ionic liquid medium - Balaraman, Ekambaram; Srinivas, Venu; Swamy, K. C. Kumara (Tetrahedron, 2009)
A simple transition metal-free hydro/hydrothiophosphonylation of Baylis–Hillman adducts, substituted allyl bromides, allenylphosphonates and alkynes, promoted by fluoride ion in ionic liquid, is described. Clear-cut evidence for fluoride activation of the phosphite via pentacoordinate phosphorus is provided for the first time. Also, in a comparative reaction, the product obtained was different from that from the palladium catalyzed one. Structures of key products are proven by X-ray crystallography.